Environmental Efficiency of Rice Farming in East Java - Rizky Zulkarnain (East Java Economic Journal, 2025)
Sustainable agriculture is not only global agenda, but also becomes national and regional agenda. Rice farming is a key factor of national food security, where East Java province has a vital role as the largest rice producer in Indonesia. Unfortunately, excessive practices in agriculture lead to detrimental impact on environment, such as greenhouse gas (GHG) emissions, land degradation and water pollution (eutrophication). This study aims to measure environmental efficiency of rice farming in East Java and also to analyze its determinants. This study employs stochastic frontier model to measure environmental efficiency as well as to examine the effects of various factors. The results shows that environmental efficiency of rice farming in East Java is generally low, with average score 0.463. This result suggests that there is opportunity to enhance environmental efficiency of rice farming in East Java by 53.7%. The low environmental efficiency is influenced by the low labor quality (education and managerial quality), low technology adoption, physical environment, and institutional environment (land ownership, counseling, credit access, social network). Based on this study, various policy interventions can be implemented to improve environmental efficiency.